Photocleavable epoxy based materials. (9th July 2015) - Radl, Simone; Kreimer, Manuel; Manhart, Jakob; Griesser, Thomas; Moser, Andreas; Pinter, Gerald; Kalinka, Gerhard; Kern, Wolfgang; Schlögl, Sandra
Abstract: The present study aims at the development of photodegradable epoxy based materials comprising o -nitrobenzyl ester links that undergo well defined bond cleavage in response to UV irradiation. New bi-functional epoxy based monomers bearing o -nitrobenzyl ester groups are synthesized and thermally cured with an anhydride hardener to yield photosensitive polymers and duromers. The UV induced changes in solubility are exploited for the preparation of positive-type photoresists. Thin patterned films are obtained by photolithographic processes and characterized by microscopic techniques. The results evidence that sensitive resist materials with good resolution and high contrast behavior can be accomplished. Along with resist technology, the applicability of o -nitrobenzyl chemistry in the design of recyclable polymer materials with thicknesses in the millimeter range is evaluated. By monitoring the thermo-mechanical properties upon UV illumination, a distinctive depletion of storage modulus and glass transition temperature is observed with increasing exposure dose. Additionally, single fiber pull-out tests are carried out revealing a significant decrease of the interfacial adhesion at the fiber-matrix interface due to the phototriggered cleavage reaction. Graphical abstract: Highlights: Synthesis of photocleavable epoxy based monomers with o -nitrobenzyl ester links. UV induced cleavage reaction is studied in epoxy based polymers and 3D networks. Conversion of nitro groups is influenced by the mobility of the polymer chains. Changes in solubility are exploited for preparation of positive-type photoresists. Applicability for thin composite materials with improved recyclability is confirmed.